Evaluation of Breast Tumor Response to Neoadjuvant Chemotherapy with Tomographic Diffuse Optical Spectroscopy: Case Studies of Tumor Region-of-Interest Changes - Jiang, Shudong; Pogue, Brian W.; Carpenter, Colin M.; Poplack, Steven P.; Wells, Wendy A.; Kogel, Christine A.; Forero, Jorge A.; Muffly, Lori S.; Schwartz, Gary N.; Paulsen, Keith D.; Kaufman, Peter A. (Radiology, 2009)
To evaluate two methods of summarizing tomographic diffuse optical spectroscopic (DOS) data through region-of-interest (ROI) analysis to differentiate complete from incomplete responses in patients with locally advanced breast cancer undergoing neoadjuvant treatment and to estimate the standard deviations of these methods for power analysis of larger study designs in the future. Subjects participating in the HIPAA-compliant imaging study, approved by the institutional review board, provided written informed consent and were compensated for their examination participation. Seven of 16 cases in women with complete study data were analyzed by using both fixed- and variable-size (full-width-at-half-maximum) ROI measures of the DOS total hemoglobin concentration (Hb(T)), blood oxygen saturation, water fraction, optical scattering amplitude, and scattering power in the ipsilateral and contralateral breasts. Postsurgical histopathologic analysis was used to categorize patients as having a complete or incomplete treatment response. Average normalized change in Hb(T) was the only DOS parameter to show significant differences (P < or = .05) in the pathologic complete response (pCR) and pathologic incomplete response (pIR) outcomes in seven patients. Mean values of the changes for fixed-size ROIs were -64.2% +/- 50.8 (standard deviation) and 16.9% +/- 38.2 for the pCR and pIR groups, respectively, and those for variable-size ROIs were -96.7% +/- 91.8, and 14.1% +/- 26.7 for the pCR and pIR groups, respectively. Tomographic DOS may provide findings predictive of therapeutic response, which could lead to superior individualized patient treatment. http://radiology.rsnajnls.org/cgi/content/full/2522081202/DC1.